In-Service Training for Secondary English Teachers of Bangladeshi Madrasahs: Investigating Adequacy and Effectiveness - Muhammed Rukan Uddin (PAROLE: Journal of Linguistics and Education, 2020)
In-service training (INSET) is crucial for language teachers who play instrumental role for effective curriculum implementation of any educational programme. Bangladesh Madrasah Teachers Training Institute (BMTTI) is the only government training institute which provides both pedagogical and administrative trainings to 1, 38, 775 madrasah teachers (BANBEIS, 2018). The question which motivated the study was whether the secondary English teachers—6553 as of 2018 (BANBEIS, 2018)—got adequate and effective pedagogical training from the institute. Having adopted the mixed-method-approach, the author administered questionnaires to 20 teachers, interviewed the three English language trainers of the institute, and analysed the training module. Findings show that INSET facilities for madrasah English teachers are clearly insufficient, and the trainings do not deliver expected outcomes due to at least four reasons: (a) inadequacy of the institute’s logistics to conduct training sessions for the required number of English teachers every year; (b) absence of permanent and professional trainers; (c) lack of motivated trainee teachers; and (d) ineffective training modules. The study implies that the madrasah education, though runs parallel with the mainstream education system in Bangladesh, has not been given required attention so far as INSET for English teachers is concerned. Since teacher training is an integral part of continuing professional development (CPD), inadequate training facilities will certainly affect CPD for the madrasah teachers which will ultimately encumber curriculum implementation. The study will have substantial impact on the future policy making with regard to the appropriateness and effectiveness of training sessions for the secondary English teachers of Bangladeshi madrasahs.